2019
DOI: 10.1186/s12889-019-7638-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of neonatal mortality in the largest international border of Brazil: a case-control study

Abstract: Background Foz do Iguassu is a Brazilian municipality located in the most populous international border of the country and provides medical care to foreigners. Neonatal mortality in the city is higher than Brazil’s average and corresponds to 61% of all deaths in children under five. The current study aimed to identify the determinants of neonatal mortality in Foz do Iguassu. Methods In this case-control study, we analyzed all neonata… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
2
19
2
1
Order By: Relevance
“…In a study by Debelew GT, et al carried out in North Gondar Zone in Northwest Ethiopia, low birth weight, lack of formal education in mothers (a reflection of low social class), neonatal illnesses, and maternal illnesses were found to be associated with neonatal death 33 . The present study did not consider maternal illness as a risk factor for neonatal mortality and other studies also have not found maternal illnesses to be a risk factor for neonatal mortality 34,35 .…”
Section: Discussioncontrasting
confidence: 71%
“…In a study by Debelew GT, et al carried out in North Gondar Zone in Northwest Ethiopia, low birth weight, lack of formal education in mothers (a reflection of low social class), neonatal illnesses, and maternal illnesses were found to be associated with neonatal death 33 . The present study did not consider maternal illness as a risk factor for neonatal mortality and other studies also have not found maternal illnesses to be a risk factor for neonatal mortality 34,35 .…”
Section: Discussioncontrasting
confidence: 71%
“…First, we did not example the contribution of antenatal factors, which have been found in other studies to contribute to NM. 10,11,13,14 In this regard it is notable that a maternal referral was associated with a 1.7 fold increased likelihood of death. Second, the report represents a single center, and the ndings may not be generalizable to other regions of Tanzania, or other low resource countries.…”
Section: Discussionmentioning
confidence: 91%
“…There are data to indicate that NM is strongly in uenced by GA and/or birth weight (BW) as well as variables during labor and the delivery room. [10][11][12][13][14][15][16][17][18] Moreover many of the prior studies have not examined NM as a function of time. This is relevant to KCMC, since a premature care bundle was introduced in that institution in 2015 and completed in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the four-time ANC was the lowest at 64% in Pidie, but the highest (96%) in Banda Aceh. When examining neonatal mortality rate against four-time ANC at the district level, it shows the negative correlation, indicating the higher percent of antenatal care, the lower neonatal mortality rate, but it was not statistically significant, rs ( 21 ) = − 0.35, P =0.09. Descriptive thematic map demonstrates variations in neonatal mortality rate and ANC across the districts in Aceh province.…”
Section: Resultsmentioning
confidence: 96%